Comparison of the Efficacy of two Different Training Methods on the Surgical Safety Checklist: A Randomized Study. - Melike Tasci, Sena; Gezginci, Elif; Goktas, Sonay (International Journal of Caring Sciences)
Aim: The aim of this study was to compare the effectiveness of structured verbal training and web-based training methods given to operating room nurses on the Surgical Safety Checklist. Methods: This randomized experimental study was conducted between June and August 2018 with fifty nurses working in the operating room unit of a private hospital in Istanbul, Turkey. The participants were divided into two equal groups: structured verbal training and web-based training by simple randomization method. The data were collected as the Pre-test and Post-test in the form of a Questionnaire prepared by the researchers using the literature on the Surgical Safety Checklist and the Personal Information Form. Post-test was performed 3 weeks after structured verbal training and web-based training methods. The data were analyzed using SPSS (Statistical Package for Social Sciences) 22.0 program. Number, percentage, median, minimum, maximum, Chi-Square test, Mann-Whitney U test and Wilcoxon test were used to evaluate the data. Results: Sixty percent of structured verbal training group and ninety two percent of web-based training group were women. A statistically significant difference was found between structured verbal training and web-based training in terms of gender, educational levels and working time in the operating room (p <0.05). While there was no statistically significant difference between the two groups before and after training given to the operating room nurses related to the Surgical Safety Checklist (p >0.05), there was a statistically significant difference between the Pre-test and Post-test in both groups (p <0.05). Conclusion: According to this study, there was no difference between structured verbal training and web-based training methods given to operating room nurses on the Surgical Safety Checklist; however, both training methods were found to be effective.